Архетипне дно вибраної лірики українських неокласиків - Смольницька, О. (Філологічний дискурс, 2018)
У статті пропонується спроба дослідити архетипне дно
вибраних віршів українських неокласиків. До уваги беруться бінарні
опозиції, свідоме і несвідоме. Застосовується компаративний аналіз.
Дослідниця продовжує юнґіанський дискурс Ніли Зборовської. Стаття
базована на здобутках літературознавства, міфологічної школи,
психоаналізу, філософії. The article proposes an attempt to explore the archetypal bottom of the selected
poems of the Ukrainian neoclassicists. Attention is drawn to the binary oppositions,
the spheres of conscious and unconscious. A comparative analysis is used. The
research proves that there is a link between the specific poems of the Ukrainian
neoclassicists and the works of other literatures (as the French or Belorussian ones)
translated by these poets. There are also patterns with the works of Lessya Ukrainka
who was discovered and comprehensively analyzed by the neoclassicists in her
European context. The study analyses the patterns, archetypes and symbols of the
Antique (Greek and Roman), Celtic (Irish) and other mythologies which are in the
neoclassical texts. The «clear» cults of Apollo and Aphrodite as symbols of the
Ukrainian neoclassicists are researched in their evolution. The article analyses the
neoclassicists of different generations. The researcher continues the Jungian
discourse of Nila Zborovska offered by this Ukrainian psychoanalyst, literature
critic and writer. The article is based on the achievements of literary studies,
mythological school, psychoanalysis, philosophy. The research has a theoretical and
practical orientation.